High-temperature long-lasting stability assessment of a single-crystal diamond detector under high-flux neutron irradiation. (28th December 2016) - Pilotti, R.; Angelone, M.; Marinelli, M.; Milani, E.; Verona-Rinati, G.; Verona, C.; Prestopino, G.; Montereali, R. M.; Vincenti, M. A.; Schooneveld, E. M.; Scherillo, A.; Pietropaolo, A.
Abstract: An innovative diamond detector layout is presented that is designed to operate at high temperature under intense neutron and gamma fluxes. It is made of a 500 μ m "electronic grade" diamond film with 100 nm thick Ag metal contacts deposited onto each surface of the film by means of thermal evaporation. A thick layer of 6 LiF has been deposited on top of one of the two Ag contacts to make the detector sensitive to thermal neutrons. The device was tested at the ISIS spallation neutron source (Rutherford Appleton Laboratory, UK) using the INES beam line. The detector was continuously irradiated for 100 hours in vacuum, exposed to a neutron flux of about 10 6 n cm −2 s −1 at a temperature . The aim of this experiment was to study the time dependence of the diamond detector performance while operating at high temperature under irradiation, providing a first experimental proof of reliable continuous operation for 100 hours at high temperature in a harsh environment.